Peningkatan Kualitas flakes Ganyong (canna edulis ker.) dan Bekatul Menggunakan Variasi Sayuran - Sukamdani, Haryo; Purwijantiningsih, L.M. Ekawati; Pranata, F. Sinung (PBI Yogyakarta, 2014)
AbstractFlakes are ready to eat cereal product in order to provide a high caloric needs for those who consume them. Utilization of ganyong into flakes is one alternative that increases the diversification of processed ganyong prospects in the community. In order to improve the nutritional quality of flakes, especially fiber, other ingredients are added for flakes. Variety of vegetables and rice brandâs is used as the main raw material of flakes. Variety of vegetables is broccoli, spinach and carrots and with the addition of vegetables can be seen the influence of increasing the nutritional value from the resulting flakes. This research used completely randomized design (CRD). The results obtained in this study of flakes product are have variations of water content 0.03-0.36%, ash 2.69-3:09%, protein 5.72-6.36%, 0.96-3.08% fat, carbohydrate 87.47-90.61%, soluble fiber 1.59-4.4%, insoluble fiber 0.01-0.02%, total fiber 1.6-4.42%, texture 3349.8-3687.8 gf and microbiological tests such total plate count, molds and yeasts and Staphylococcus aureus that meets the ISO standard of cereal (SNI 01-4270 -1996). The results showed that the carrot flakes had the highest quality overall and flakes broccoli had the highest fiber content.Key words: Flakes, ganyong, variety of vegetables, rice branâsAbstrakFlakes adalah produk makanan siap saji untuk menyediakan kalori bagi yang mengkonsumsinya. Pemanfaatan ganyong sebagai produk sereal adalah salah satu cara meningkatkan diversifikasi pangan di masyarakat. Dalam rangka meningkatkan kualitas gizi flakes, terutama serat maka bahan lain ditambahkan dalam pembuatan flakes. Variasi sayuran dan bekatul digunakan sebagai bahan baku utama pembuatan flakes. Variasi sayuran yang digunakan yakni brokoli, bayam dan wortel. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL). Hasil yang didapatkan dari penelitian ini yakni kadar air flakes 0,03-0,36%, kadar abu 2,69-3,09%, protein 5,72-6,36%, lemak 0,96-3,08%, karbohidrat 87,47-90,61%, serat larut 1,59-4,4%, serat tidak larut 0,01-0,02%, total serat 1,6-4,42%, tingkat kekerasan/ tekstur 3349,8-3687,8 gf dan tes mikrobiologi seperti angka lempeng total, kapang dan khamir, serta Staphylococcus aureus sesuai standar ISO sereal (SNI 01-4270 -1996). Hasil penelitian menunjukan bahwa flakes wortel mempunyai kualitas gizi tertinggi dan flakes brokoli mengandung serat tertinggi.Kata kunci: Flakes, ganyong, variasi sayuran, bekatul